Activeness as a Virtue and Expression of the Authority of a Teacher - Tijūnėlienė, Ona (Acta Paedagogica Vilnensia, 2001)
The article raises the importance of the activeness of the teacher. Looking to activeness of a teacher as a virtue and the expression of authority, reveals the activity of physiological, psychological and ontological grounds. At the same time it reveals the role that the active teacher has in educating the younger generation and to the public welfare.